Primeness and Primitivity Conditions for Twisted Group $C^*$-Algebras - Omland, Tron Ånen (MATHEMATICA SCANDINAVICA, 2014)
For a multiplier (2-cocycle) $σ$ on a discrete group $G$ we give conditions for which the twisted group $C^*$-algebra associated with the pair $(G,σ)$ is prime or primitive. We also discuss how these conditions behave on direct products and free products of groups.